Phytosome: a novel dosage form for herbal drug delivery - Choudhury, Ananta; Verma, Swati; Roy, Amit (Creative Pharma Assent, 2014)
Phytosome is a complex of a natural active ingredient and phospholipids. The term ‘Phyto’ means plant while ‘some’ means cell like structure. It is claimed that phytosome increases absorption of